Heritability estimates of meat sensory characteristics are a function of the number of panellists and their inter-correlations. (July 2018) - Judge, M.M.; Conroy, S.; Pabiou, T.; Cromie, A.R.; Berry, D.P.
Abstract: The objective of the present study was to quantify, using simulated data, the impact on estimated heritability of varying the number of panellists and their inter-correlations using meat sensory tenderness in cattle as an example. Estimated parameters from actual sensory-based tenderness scores from 9 individual panellists on 1252 beef cattle were used to parameterise the simulation. A single "tenderness score" for each of 10 panellists was simulated for 15, 000 cattle. Heritability estimates were calculated for each of the 10 panellists individually as well as the mean score per animal for all n combinations of panellists. Heritability estimates improved with increasing number of panellists in line with expectations from a deterministic equation. The increase in heritability was due to a reduction in the residual variance, albeit the rate of reduction in residual variance declined with each additional panellist included in the calculated mean tenderness score. Results highlight the importance of reporting the number of panellist scores per animal as well as their inter-correlations in sensory-based studies. Highlights: Heritability estimates for tenderness improved with increasing number of panellists. Genetic studies should report the number of panellists and their inter-correlations. Little value in heritability estimates exist from using >6 panellists. Consideration should be taken of number of panellists when merging data.